The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/ijc.30490
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism of rs763110 polymorphism contributing to cervical cancer risk by affecting the binding affinity of C/EBPβ and OCT1 complex to chromatin

Abstract: Recently, several studies have showed that FAS (rs2234767, rs1800682) and FASL (rs763110) functional single nucleotide polymorphisms (SNPs) were associated with the risk of various cancers. However, the association between cervical cancer risk and the three SNPs above remained inconclusive. In this work, we performed a two-stage case-control study on 1155 cervical cancer patients and 1252 matched healthy controls to determine the roles of the mentioned SNPs in cervical cancer susceptibility. We genotyped the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
2
8
0
2
Order By: Relevance
“…Further siRNA knockdown experiments showed that Krox-20 was recruited to Sp1 binding motif in both HeLa (HPV18–positive), SiHa (HPV16–positive), and C–33A (HPV–negative) cervical cancer cells in vitro knockdown experiments. This also confirmed that HPVs infection is not a necessary Etiological Factor for cervical cancer proposed by Wu et al [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…Further siRNA knockdown experiments showed that Krox-20 was recruited to Sp1 binding motif in both HeLa (HPV18–positive), SiHa (HPV16–positive), and C–33A (HPV–negative) cervical cancer cells in vitro knockdown experiments. This also confirmed that HPVs infection is not a necessary Etiological Factor for cervical cancer proposed by Wu et al [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…21 Briefly, the following antibodies were used for the immunoprecipitation reaction: Sp1, NF1, positive control RNA poly (Active Motif, Carlsbad, CA, USA) or negative control IgG (Active Motif, Carlsbad, CA, USA). 21 Briefly, the following antibodies were used for the immunoprecipitation reaction: Sp1, NF1, positive control RNA poly (Active Motif, Carlsbad, CA, USA) or negative control IgG (Active Motif, Carlsbad, CA, USA).…”
Section: Chromatin Immunoprecipitation Assay (Chip)mentioning
confidence: 99%
“…Human peripheral white blood and colorectal cancer cells were used for ChIP assay with a ChIP-IT TM Express Magnetic Assay kit and ChIP-IT TM Control qPCR kit (Active Motif, Carlsbad, CA, USA) as described previously. 21 Briefly, the following antibodies were used for the immunoprecipitation reaction: Sp1, NF1, positive control RNA poly (Active Motif, Carlsbad, CA, USA) or negative control IgG (Active Motif, Carlsbad, CA, USA). The precipitated genomic DNA was analyzed by quantitative RT-PCR with the following DR4 promoter primers including the rs13278062 polymorphism: 5 0 -CCTCAGCCTTTCTGTGACCC-3 0 (forward) and 5 0 -AAATCGCTTGAACCTGGGAG-3 0 (reverse).…”
Section: Chromatin Immunoprecipitation Assay (Chip)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that approximately 500,000 new cases of cervical cancer are reported annually and about 230,000 women die of cervical cancer annually [4] . Cervical cancer is a complex disease involving the abnormal expression of many oncogenes and tumor suppressor genes [5] , [6] , [7] , [8] . Previous studies have revealed several genes associated with human cervical cancer [9] , [10] , [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%